2019
DOI: 10.1016/j.thromres.2018.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Women's views, adherence and experience with postnatal thromboprophylaxis

Abstract: IntroductionBased on current guidelines, many women qualify for postnatal thromboprophylaxis following childbirth, however, little information exists on how adherent women are and their experiences to both pharmacological and mechanical forms of thromboprophylaxis. Materials and MethodsWomen requiring postnatal thromboprophylaxis were given questionnaire packs exploring their beliefs about enoxaparin, anti-embolic stockings (AES) and intermittent pneumatic compression devices (IPCD). Women were also asked to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 28 publications
1
29
0
Order By: Relevance
“…Our study showed an adherence rate of 78.8% among parturients' who underwent CS. This is consistent with previously published studies [ 11 , 14 , 15 , 21 ]. Considering the risk of VTEs following CS, this rate of adherence is reassuring [ 10 ].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Our study showed an adherence rate of 78.8% among parturients' who underwent CS. This is consistent with previously published studies [ 11 , 14 , 15 , 21 ]. Considering the risk of VTEs following CS, this rate of adherence is reassuring [ 10 ].…”
Section: Discussionsupporting
confidence: 94%
“…Concerning the sample size, per our institution statistics, there are around 1000 C-section deliveries per year, with a power of 90%, and an adherence rate of 82% a sample of 138 participants would be needed. [ 11 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has demonstrated that using methods to systematically incorporate the user perspective early in the design process can result in the development of a device which is safe, effective and used by the patient. 44 Research more widely in the field that examined the use of a modern IPC device demonstrates that it is possible to develop comfortable devices 45 with 86% (26/30) of patients reporting it was comfortable and that they would use it again if required. Two studies 35 42 within this review reported adherence levels when studying different machine designs and one study focused on the length of IPC sleeve 30 and its effect on adherence with knee length sleeves being adhered to to a greater degree.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, as there are no clinical data to evaluate IPC in the postpartum period, the role of mechanical thromboprophylaxis in this setting is unclear. Also, one study pointed out a low adherence with compression stockings, after hospital discharge, highlighting its burden despite its safety ( 46 ).…”
Section: How Can We Prevent Postpartum Vte In High-risk Situations?mentioning
confidence: 99%